2007
DOI: 10.1007/s11095-007-9408-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug Elimination Kinetics Following Subconjunctival Injection Using Dynamic Contrast-Enhanced Magnetic Resonance Imaging

Abstract: DCE-MRI was used to quantitatively compare the subconjunctival clearance rates of Gd-DTPA and Gd-albumin. Dynamic clearance mechanisms present in vivo significantly reduced the subconjunctival concentration of Gd-DTPA but not Gd-albumin. Lymphatic clearance does not seem to be as significant as clearance by blood, as evidenced by data from Gd-albumin injections. Larger injection volumes may allow for longer retention times and prolonged release of drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 27 publications
4
45
1
Order By: Relevance
“…For small molecules, their half-lives in the subconjunctival space are in the order of 10–40 min. The main mechanisms of ocular clearance following subconjunctival injection are lymphatic and blood clearance in the periocular space (29,32,33). In the present study, pRNA nanoparticles were distributed from the injection sites to different ocular tissues (conjunctiva, cornea, retina, and sclera) and then cleared from the eyes rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…For small molecules, their half-lives in the subconjunctival space are in the order of 10–40 min. The main mechanisms of ocular clearance following subconjunctival injection are lymphatic and blood clearance in the periocular space (29,32,33). In the present study, pRNA nanoparticles were distributed from the injection sites to different ocular tissues (conjunctiva, cornea, retina, and sclera) and then cleared from the eyes rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is unknown whether the conclusions reached in the rabbit can be directly used in human eyes, as the intravital studies in human beings are limited. Furthermore, these methods fail to sufficiently reveal the theoretical system of drug metabolism in eyes [13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental techniques are not clinically suitable due to their invasion and radioactivity. MRI technique can not only provide anatomical information but also make quantitative analyses possible [13] . Our research expands the application of MRI to studies of the permeability of medicines in the eye and found MR technology is superior to other methods in assessing drug permeability in the ocular region.…”
Section: Discussionmentioning
confidence: 99%
“…However, data in the literature have shown that the half-life of small molecules in periocular regions or more specifically in the subconjunctival space is on the order of 10 min after local injection, and the short half-life is presumably caused by considerable drug clearance via both blood and lymph microvessels. 1,18,41,42 These data indicate that after topical application, the majority of ECA molecules are absorbed by the microvessels if they diffuse into the subconjunctival space via conjunctiva. Therefore, we neglected the diffusion of ECA from the subconjunctival space into the sclera.…”
Section: Concentration Boundary Conditionsmentioning
confidence: 90%